Critical Discourse Analysis Of Human Rights Violations In The Washington Post And New York Times Online Newspapers: Post Isis Iraq Era - Qaysi, Fouad Hussein Ali Al (2024)
The present study investigated the depiction of human rights violations in iraq post-isis era in the american online newspapers, particularly violating the right to peaceful assembly through the demonstrations that occurred in 2019. This study focused on examining the macro- and micro- semantic structures of the news articles and ideological representations through employing van dijk‘s (1980) approach to semantic macrostructure and van dijk‘s (1998) theory of ideology. Furthermore, the historical background information and political critique were presented through applying wodak‘s (2001) discourse historical theory to facilitate discourse interpretation and maintain objectivity in the analytical process. The data was collected from 6 articles in each of the two american online newspapers, namely, the washington post and new york times news in 2019. Analytically, the macro-level revealed an agreement between both newpapers on the thematic structure about hrvs in iraq, stating that the protests in iraq on demanding basic rights, were dealt with violently by the government, leading to the government's fall.